THE EFFECT OF SERVICE QUALITY ON SATISFACTION AND ITS IMPACT ON STUDENT LOYALTY IN BATURAJA EDUCATION, OGAN KOMERING ULU DISTRICT - Gamma M Al Pome; Diah Isnani Asiati; Choiriyah Choiriyah (STIE DWI SAKTI BATURAJA, 2021)
This study entitled The Effect of Service Quality on Satisfaction and Its Impact on Student Loyalty at Baturaja College, Ogan Komering Ulu Regency. This research method uses descriptive and inferential statistical analysis, with the path analysis model. The results of the study answer the formulation of the problem which is also the purpose of this study. Through the calculation of the CR-value in accordance with the hypothesis, this study concludes, firstly, there is a positive and significant effect of Service Quality on Student Satisfaction. Second, there is a positive and significant effect of Service Quality on Student Loyalty. Third, there is the influence of student satisfaction on student loyalty. Fourth, responsiveness has a positive and insignificant effect on student loyalty. Fifth, satisfaction has a positive and insignificant effect on student loyalty. Sixth, assurance / certainty on satisfaction and its impact on loyalty has a positive and insignificant effect on students at Baturaja College, Ogan Komering Ulu Regency